Resources for health: differential effects of optimistic self-beliefs and social support according to socioeconomic status - Schöllgen, Ina; Huxhold, Oliver; Schüz, Benjamin Ernst Christoph; Tesch-Römer, Clemens (Health psychology, 2011)
Objective: This study examined whether socioeconomic status (SES) determines the degree to which psychological and social resources such as optimistic self-beliefs and social support affect health. Design: We used data from the representative German Ageing Survey (N = 2,454, aged 40-85 years). Structural equation modeling was employed to examine whether relationships between psychological (self-esteem, control beliefs, optimism) and social resources (perceived emotional and informational support, network size) and health differ between education and income groups. Main Outcome Measures: Self-reported physical health, functional health, and subjective health. Results: Psychological resources positively affected health in all groups but were stronger predictors of functional and subjective health in low compared to higher educated participants. A higher level of social resources was associated with better functional and subjective health mainly in the low-income group. Social resources were particularly important for financially disadvantaged older people. Conclusion: Our results provide evidence for differential effects of optimistic self-beliefs and social support on health depending on whether individuals are challenged by low incomes or low education. Future research, especially aimed at intervention, should consider that different aspects of SES have differential meanings and that the impact of health-protective factors may vary according to SES facet. (PsycInfo Database Record (c) 2020 APA, all rights reserved)